2016
DOI: 10.5603/fm.a2016.0017
|View full text |Cite
|
Sign up to set email alerts
|

Renal artery entrapment — anatomical risk factors rating

Abstract: p < 0.033 (Folia Morphol 2016; 75, 4: 486-492)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Most cases of renal entrapment are results of musculotendinous fibres, hypertrophic diaphragmatic crus or high ectopic renal artery origin. (Arazińska et al 2016) This case is extraordinary because the left renal artery is compressed by the inferior mesenteric artery. The patient may not have suffered any symptoms due to adequate perfusion of the kidney, being a consequence of fusion and presence of two other arteries.…”
Section: Discussionmentioning
confidence: 98%
“…Most cases of renal entrapment are results of musculotendinous fibres, hypertrophic diaphragmatic crus or high ectopic renal artery origin. (Arazińska et al 2016) This case is extraordinary because the left renal artery is compressed by the inferior mesenteric artery. The patient may not have suffered any symptoms due to adequate perfusion of the kidney, being a consequence of fusion and presence of two other arteries.…”
Section: Discussionmentioning
confidence: 98%
“…In a study on 204 computed tomography images, Arazińska et al [34] reported a mean RA-CT distance of 25.53±6.59 mm. On the other hand, measurements performed in males aged 18 to 45 years showed that the distance between RA and CT was 16-129 mm (mean, 33 mm) and the distance between RA and AB was 66-123 mm (mean, 97 mm) [35].…”
Section: Distances Of Renal Arteries To Ct and Abmentioning
confidence: 99%
“…The ligament is highly variable with an appearance ranging from a well‐defined ligamentous mass to an amorphous area of connective tissue. In some patients, low insertion or high origin of the celiac or renal artery relative to the MAL may cause extrinsic compression of the celiac, mesenteric (Kopecky et al, ; Ilica et al, ; Matusz et al, ), and renal arteries (Ilica et al, ; Arazińska et al, ), as well as, the aorta (Curl et al, ). Compression of the celiac axis by the median arcuate ligament produces characteristic findings that are visible on CT angiography, which demonstrates a characteristic focal narrowing in the proximal celiac axis.…”
Section: Introductionmentioning
confidence: 99%